2011
DOI: 10.1002/jms.2019
|View full text |Cite
|
Sign up to set email alerts
|

Tandem mass spectrometry of platinated quadruplex DNA

Abstract: Quadruplexes are higher-order structures formed by G-rich DNA strands that are involved in various processes of cell cycle regulation, such as control of telomere length and participation in gene regulation. Because of these central biological functions, quadruplex DNA represents a promising target for cancer therapy, e.g. by applying organometallic drugs, such as cisplatin. High-resolution electrospray tandem mass spectrometry is evaluated as a technique for exploring structural features of unplatinated and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 47 publications
0
26
0
1
Order By: Relevance
“…Electrospray mass spectrometry was demonstrated by several research groups to be a suitable tool for exploring the in vitro formation of tetra-, bi-, and monomolecular quadruplexes [25][26][27][28] and even mechanistic data were provided about the gas-phase dissociation of these intriguing higher-order structures. [15,26,29] In a recent study, we reported on the investigation of the dissociation behavior of quadruplex DNA and cisplatin adducts thereof by high-resolution electrospray tandem mass spectrometry. [29] The (unplatinated) tetramolecular assembly [d(TG 6 T) 4 + 5 NH 4 + ] (see inset in Fig.…”
Section: Interaction Of Cisplatin With Single-stranded Nucleic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrospray mass spectrometry was demonstrated by several research groups to be a suitable tool for exploring the in vitro formation of tetra-, bi-, and monomolecular quadruplexes [25][26][27][28] and even mechanistic data were provided about the gas-phase dissociation of these intriguing higher-order structures. [15,26,29] In a recent study, we reported on the investigation of the dissociation behavior of quadruplex DNA and cisplatin adducts thereof by high-resolution electrospray tandem mass spectrometry. [29] The (unplatinated) tetramolecular assembly [d(TG 6 T) 4 + 5 NH 4 + ] (see inset in Fig.…”
Section: Interaction Of Cisplatin With Single-stranded Nucleic Acidsmentioning
confidence: 99%
“…[15,26,29] In a recent study, we reported on the investigation of the dissociation behavior of quadruplex DNA and cisplatin adducts thereof by high-resolution electrospray tandem mass spectrometry. [29] The (unplatinated) tetramolecular assembly [d(TG 6 T) 4 + 5 NH 4 + ] (see inset in Fig. 4) served as a first model compound laying the basis for the detailed characterization of the interaction of transition metal-based anti-cancer drugs with quadruplex DNA.…”
Section: Interaction Of Cisplatin With Single-stranded Nucleic Acidsmentioning
confidence: 99%
“…[276] Tandem mass spectrometry using CID fragmentation experiments were reported by Schürch et al to explore structural modification of mono-, bi-and tetra-molecular quadruplexes exposed to cisplatin. [277] By comparison with CD experiments, it was concluded that peaks of un-annealed single strands could not be attributed to decomposition of the structures upon ionization but rather to incomplete quadruplex formation prior to the measurements. For each of the three types of quadruplexes, exhibiting different structural features, the platination stoichiometry and rate of binding were found to be very different.…”
Section: Dna G-quadruplexesmentioning
confidence: 99%
“…Identification of the platination sites on the monomolecular structure was possible, and the terminal G-repeats sequences were determined to be the favourable metallation sites. [277] Interestingly …”
Section: Dna G-quadruplexesmentioning
confidence: 99%
“…demonstrated that the enhanced cleavage of the 3’-C-O bond next to a GG site in oligodeoxyribonucleotides was catalyzed by the adjacent cisplatin adduction site, as revealed by the formation of a highly characteristic w ion [42]. This same group also elucidated the fragmentation pathways of platinated quadruplex DNA [43] and RNA [44]. More recently, our group reported a comparison of MS/MS methods, including CID, IRMPD (10.6 μm), ETD, NETD and UVPD (193 nm) as well as hybrid MS/MS processes [45], termed ETcaD, ET-IRMPD and ET-UVPD, for characterization of DNA/cisplatin adducts [46].…”
Section: Introductionmentioning
confidence: 99%